An ethnographic organisational study of alongside midwifery units: a follow-on study from the Birthplace in England programme - Christine McCourt; Juliet Rayment; Susanna Rance; Jane Sandall (National Institute for Health Research, 2014)
Background: Alongside midwifery units (AMUs) were identified as a novel hybrid organisational form in the Birthplace in England Research Programme, to which this is a follow-on study. The number of such units (also known as hospital birth centres) has increased greatly in the UK since 2007. They provide midwife-led care to low-risk women adjacent to maternity units run by obstetricians, aiming to provide a homely environment to support normal childbirth. Women are transferred to the obstetric unit (OU) if they want an epidural or if complications occur. Aims: This study aimed to investigate the ways that AMUs in England are organised, staffed and managed. It also aimed to look at the experiences of women receiving maternity care in an AMU and the views and experiences of maternity staff, including both those who work in an AMU and those in the adjacent OU. Methods: An organisational ethnography approach was used, incorporating case studies of four AMUs, selected for maximum variation on the basis of geographical context, length of establishment of an AMU, size of unit, management, leadership and physical design. Interviews were conducted between December 2011 and October 2012 with service managers and key stakeholders (n = 35), with professionals working within and in relation to AMUs (n = 54) and with postnatal women and birth partners (n = 47). Observations were conducted of key decision-making points in the service (n = 20) and relevant service documents and guidelines were collected and reviewed. Findings: Women and their families valued AMU care highly for its relaxed and comfortable environment, in which they felt cared for and valued, and for its support for normal birth. However, key points of transition for women could pose threats to equity of access and quality of their care, such as information and preparation for AMU care, and gaining admission in labour and transfer out of the unit. Midwives working in AMUs highly valued the environment, approach and the opportunity to exercise greater professional autonomy, but relations between units could also be experienced as problematic and as threats to professional autonomy as well as to quality and safety of care. We identified key themes that pose potential challenges for the quality, safety and sustainability of AMU care: boundary work and management, professional issues, staffing models and relationships, skills and confidence, and information and access for women. Conclusions: AMUs have a role to play in contributing to service quality and safety. They provide care that is satisfying for women, their partners and families and for health professionals, and they facilitate appropriate care pathways and professional roles and skills. There is a potential for AMUs to provide equitable access to midwife-led care when midwifery unit care is the default option (opt-out) for all healthy women. The Birthplace in England study indicated that AMUs provide safe and cost-effective care. However, the opportunity to plan to birth in an AMU is not yet available to all eligible women, and is often an opt-in service, which may limit access. The alignment of physical, philosophical and professional boundaries is inherent in the rationale for AMU provision, but poses challenges for managing the service to ensure key safety features of quality and safety are maintained. We discuss some key issues that may be relevant to managers in seeking to respond to such challenges, including professional education, inter- and intraprofessional communication, relationships and teamwork, integrated models of midwifery and women's care pathways. Further work is recommended to examine approaches to scaling up of midwifery unit provision, including staffing and support models. Research is also recommended on how to support women effectively in early labour and on provision of evidence-based and supportive information for women. Funding: The National Institute for Health Research Health Services and Delivery Research programme.